From Virtual to Physical - Irena Reimannová; Kateřina Keplová (Charles University, 2024)
Since the beginning of the third decade of the 21st century, teachers of all levels of education have been experiencing turbulent times. Beginner teachers as well as experienced ones have been forced to rethink their skillset to reflect the changes not only in opportunities provided by the development of technology and globalisation but also the sudden, unexpected consequences of the global pandemic. The governmental decision to close all educational institutions in the Czech Republic because of the COVID-19 pandemic and to move the teaching and learning process into an online environment had an impact on university initial teacher education for future teachers of English, among others. Everyone had to cope with the challenges the situation brought about; educators had to re-evaluate their approach to initial teacher education so that their students would feel better prepared for the challenges of the crisis. Teacher educators, among others, have embraced the changing environment and have been actively searching for ways to best support students in their preparation for the teaching profession. The aim of this paper is to present and discuss the results of research conducted at the Department of English and American Studies at a regional Czech university in response to the consequences of the pandemic. The aim of the small-scale study was to explore student teachers' perceptions of whether and how their microteaching sessions, conducted online because of the pandemic restrictions, prepared them for their face-to-face placement practice teaching the following semester. The context, therefore, was heavily influenced by the circumstances of the global pandemic. The theoretical framework of the initial English language teacher education programme, and of this paper, is based on the models of teacher professionalism (Spilková, 2019), the reflective practitioner (Černá, Píšová, & Vlčková, 2017), and the realistic approach (Korthagen et al., 2001). In the study, the data from reflection sessions, two focus group discussions, and a questionnaire were collected, analysed, and evaluated. The participants in the study were second-year bachelor students of the English for Education programme. The results of the research indicate that the students did not see the aims and content of the selected study programme as being affected by changes of external conditions; however, the processes of their professional learning were perceived as having been affected. These outcomes are in alignment with the research of Yochanna and Levy (2022) into the effective implementation of microteaching practice in teacher preparation. The implications of this study, in terms of both education and research, suggest that initial teacher education for future teachers of English needs to address the challenge of enabling the students to get ready for their profession regardless of whether they are teaching online or face-to-face classes. Initial teacher education should aim to prepare future teachers to expect the unexpected, which is a theme to be explored in further research.